SET: Still a Relevant Theory for the Future of Work. Issue 3 (20th September 2018) - Kurtessis, James N.; Northon, Lindsay; Streets, Valerie N.
Abstract : Few would argue that the workplace has changed tremendously over a short period of time and will continue to evolve in the years to come. Regardless of whether change is major or minor, lightning fast or painfully slow, change in and of itself may not be sufficient cause for substantial revision of existing theories, such as social exchange theory (SET); the formulation of entirely new theories; or the creation of new constructs. This is for two reasons: (a) the possibility that we overestimate the impact of change on the workplace, and (b) change can be readily incorporated into our existing theories. We expand on each of these points below and describe several possible macrolevel trends that may impact SET in the years to come.